1995
DOI: 10.1021/ja00133a035
|View full text |Cite
|
Sign up to set email alerts
|

A de Novo Designed Protein Mimics the Native State of Natural Proteins

Abstract: The de novo design of a protein that mimics the properties of natural proteins is an important goal.',2 Although some progress has been made in the design of coiled coils,3 including a de novo designed peptide with native-like behavior,3b all globular proteins designed to date appear to show some of the features of molten globule^.^ Here, we describe a peptide that self-assembles into a protein with native-like physical properties. This was achieved by a strategy which included not only interactions that stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 0 publications
8
110
1
Order By: Relevance
“…These proteins tend to be extremely stable, but lack structural uniqueness, as evidenced by a variety of experimental determinants, including rapid HID exchange (Handel et al, 1993). The introduction of buried or interfacial salt bridges or polar groups in these designed proteins imparts specificity to the fold and greater resistance to exchange, despite the fact that stability is generally sacrificed (O'Shea et al, 1991;Handel et al, 1993;Lumb & Kim, 1995;Raleigh et al, 1995). In the case of the E47 homodimer, three acidic residues (Asp 21, Glu 24, and Glu 28) lie along one face of helix 1 close to helix 2', whereas basic residues (R20, R27, and R31) lie on the face nearest helix 2.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins tend to be extremely stable, but lack structural uniqueness, as evidenced by a variety of experimental determinants, including rapid HID exchange (Handel et al, 1993). The introduction of buried or interfacial salt bridges or polar groups in these designed proteins imparts specificity to the fold and greater resistance to exchange, despite the fact that stability is generally sacrificed (O'Shea et al, 1991;Handel et al, 1993;Lumb & Kim, 1995;Raleigh et al, 1995). In the case of the E47 homodimer, three acidic residues (Asp 21, Glu 24, and Glu 28) lie along one face of helix 1 close to helix 2', whereas basic residues (R20, R27, and R31) lie on the face nearest helix 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have shown that it is possible to design four-helix bundle proteins with native-like properties considering principally the intrinsic propensities and the pattern of polar and non polar amino acids. [16][17][18][19][20][21] It is worth noting that all these protein design studies relied also on the rational choice of specific interresidue contacts (to optimize the packing within the hydrophobic core) as well as on the explicit definition of the turn regions. A more general, combinatorial approach to de novo protein design was introduced by Hecht and coworkers who synthesized several four-helix bundle proteins, with native-like properties, using sequences composed from a set of amino acids with high helical propensities and with fold-appropriate patterning.…”
Section: Introductionmentioning
confidence: 99%
“…(4) is shown by simulations of experimental relaxation dispersion data collected for the 13 C α of Leu-6 of the de novo designed protein α 2 D. 105 , 106 This protein is a dimeric four-helix bundle that has all the hallmarks of a native-like protein. 107 -110 α 2 D undergoes conformational exchange between an unfolded monomer and a folded dimer species. 108 Thus the chemical shift exchange contributions to the NMR resonances of α 2 D arise from its folding; the rate constants of which were determined from global analysis of relaxation dispersion data collected at B 0 = 11.7 T and 14.1 T. 105 In the simulations presented here, three of the four parameters described in Eq.…”
Section: Sensitivity Analysis For Eq (4)mentioning
confidence: 99%